CTK Insights

24 Feb

The Joy of Homogeneity

In a recent blog A Lovely Observation Gary Davis (@RepublicOfMath) elaborated on an observation of Ben Vitale (@BenVitale) to the effect that

\frac{1+3}{5+7}=\frac{1+3+5}{7+9+11}=\frac{1+3+5+7}{9+11+13+15}= \ldots = \frac{1}{3}.

In the fractions both numerators and denominators are sums of successive odd numbers: the numerators start with 1, the denominators where the numerators leave off. Thus naturally derivation of the formula for the sum of successive odd numbers is the key to the explanation of Ben Vitale's observation. There are ways and ways to obtain the required expression. The most elementary one is to observe that

S(n) = 1 + 3 + \ldots + (2n - 1)

is the sum of an arithmetic sequence a, a + d, a + 2d, \ldots, a + (n-1)d,
where a = 1 and d = 2. With a nod to the young F. Gauss,

a+ (a + d)+(a + 2d)+ \ldots + [a + (n-1)d] = \frac{n(2a + (n-1)d)}{2},

which in the case of odd numbers gives

1+3+ \ldots + (2n-1) = \frac{n(2 + (n-1)2)n}{2}=n^2.

Another way to derive that formula is to noticee that the sum of odd numbers is the sum of all numbers less the sum of the even ones. It is convenient at this point to start using the symbol of \sum to make the formulas shorter and more manageable:


and, for the sum of all integers from 1 to n,


Now a little of summation magic:

\begin{align}S(n) &= N(2n) - 2N(n) = \sum_{k=1}^{2n}k - 2\sum_{k=1}^{n}k \\ &= \sum_{k=1}^{2n}k - \sum_{k=1}^{n}(2k)\\& = \frac{2n(2n+1)}{2}-2\frac{n(n+1)}{2}=(2n^{2}+n)-(n^{2}+n)=n^2,\end{align}

with the same result. Let's note that here we made a subtle use of the homogeneity property of function f(x) = x, namely f(2x)=2f(x). Simple as it appears, it was central to the derivation. For Ben Vitale's observation we'll have to do something very similar:

\begin{align}(2n+1)+(2n+3)+\ldots +(2n + (2n-1)) &= \sum_{k=1}^{2n}(2k-1)-\sum_{k=1}^{n}(2k-1) \\&= (2n)^2-n^2=3n^2.\end{align}

Ben Vitale's observation comes to

\frac{1+2+\ldots +(2n-1)}{(2n+1)+(2n+3)+\ldots +(4n-1)}=\frac{n^2}{3n^2}=\frac{1}{3}.

A generalization of this would be to take, say, twice as many terms in the denominator as in the numerator. This can be done in more than one way:

\frac{1+3+\ldots +(2n-1)}{1+3+\ldots +(4n-1)}=\frac{1}{4}


\frac{1+3+\ldots +(2n-1)}{(2n+1)+(2n+3)+\ldots +(6n-1)}=\frac{1}{8},

because \sum_{k=1}^{3n}(2k-1)=(3n)^2-n^2=8n^2, as before. Going further, there are at least three ways to have three times as many terms in the denominator as in the numerator:

\frac{\sum_{k=1}^{n}(2k-1)}{\sum_{k=1}^{3n}(2k-1)},\space \frac{\sum_{k=n+1}^{2n}(2k-1)}{\sum_{k=1}^{3n}(2k-1)},\space \frac{\sum_{k=2n+1}^{3n}(2k-1)}{\sum_{k=1}^{3n}(2k-1)}.

One can easily check that the three fractions are equal to \frac{1}{9}, \frac{1}{3}, and \frac{5}{9}, respectively.

Obviously, our success in getting a simple expression is due to the homogeneity of function g(x)=x^2: g(ax)=a^{2}g(x). (There is a difference between the two functions f and g. For the obvious reasons, the former is said to be homogeneous of order (degree) 1, the later of order 2.)

As Gary Davis notes at the end of his post, this kind of algebraic manipulations is accessible to middle and high school students. An additional example of the infinite series of the reciprocals of squares requires no more effort but a little hand-waving if not presented at the beginning Calculus class.

Assume we know that

\sum_{k=1}^{\infty}k^{-2}=1+\frac{1}{2^2}+\frac{1}{3^2}+\ldots =\frac{\pi^2}{6}.

Then of course, for the series that involves only even numbers,

\sum_{k=1}^{\infty}(2k)^{-2}=\frac{1}{2^2}+\frac{1}{(2^{2})(2^{2})}+\frac{1}{(2^{2})(3^{2})}+\ldots =\frac{\pi^2}{4\cdot 6}=\frac{\pi^2}{24}.

As a reward for the effort, we get an expression for the series of the reciprocals of the squares of odd numbers:


Who would have thought that the series of the reciprocals of odd squares sums up to three times a similar series for even squares!

7 Responses to “The Joy of Homogeneity”

  1. 1
    Eric Hsu Says:

    Nice problem! The sum of odd numbers version has a nice visual answer. First, sum of 2n odd numbers can be famously represented as the Ls of a 2n x 2n square. (compare http://merganser.math.gvsu.edu/calculus/summation/odds.html). Then the numerator is the sum of first n of these, which form a smaller n x n square, which can be seen as a quarter of the larger square. So the denominator is three times larger than the numerator.

  2. 2
    admin Says:

    Thank you Eric. Have not thought of that in geometric terms.

  3. 3
    Allen Says:

    Thanks! Nice to see this problem. I've also noticed that (1+3+5+7+...+n)/(n+(n+2)+(n+4)+...+(2n-1))=a/b where a+b = 2n or n depending on if n is of the form 4i+1 or 4i+3 (where i is a natural number)
    For example: let n=4i+1 = 13 (i=3), then (1+3+5+7+9+11+13)/(13+15+17+19+21+23+25)=49/133 = 7/19, and 7+19=26=2n
    If n=4i+3=15 (i=3), then
    (1+3+5+7+9+11+13+15)/(15+17+19+21+23+25+27+29)=64/176=4/11, and 4+11 =15=n.
    These properties can be proven using the same techniques used in your blog.

  4. 4
    admin Says:

    Allen, this is a curious property. But just to check, what about



    (1+3+...+15)/(11+13+..+25) ?

  5. 5
    Allen Says:

    For your first example, n=11 or it fits the form 4i+3 when i=2, so (1+3+...+11)/(11+13...+21)=36/96=3/8, and 3+8 = 11 = n.

    Your second example doesn't seem to fit the pattern I noticed. The largest term in the numerator (15) needs to be the same as the smallest term in the denominator(11). In other words, if the numerator sum ends with n, then the denominator sum needs to begin with n.

  6. 6
    admin Says:

    I see. Thank you, Allen. Now it's time to prove that property.

  7. 7
    admin Says:

    In the next post http://www.mathteacherctk.com/blog/2012/03/the-joy-of-homogeneity-a-sequel/ I prove this property

Leave a Reply

Time limit is exhausted. Please reload the CAPTCHA.

© 2018 CTK Insights | Entries (RSS) and Comments (RSS)

Powered by Wordpress, design by Web4 Sudoku, based on Pinkline by GPS Gazette